Bioavailability of metals in sediments and fish in agricultural and urban areas of the Pirapó river: potential toxicity and environmental monitoring - Leite, Edilaine Corrêa; Santos de Farias, Rian Richard; Cagni, Gilsemara dos Santos; Bello, José Roberto; da Silva , Thaila Fernanda Oliveira; Lizama, Maria de los Angeles Perez; Velho, Luiz Felipe Machado; Gonçalves, José Eduardo (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The level of anthropogenic interference in aquatic environments, based on the unbridled use of resources and actions incompatible with the balance in the various types of ecosystems, has triggered important research. Studies have shown that fish and sediments can be used as a tool for biomonitoring, as they demonstrate the ability to accumulate metals. Thus, to investigate the level of ecological disturbance due to contamination by metals, mainly heavy metals in the Pirapó River Basin in Paraná state (PR), the quantification of the elements Al, As, Hg, Zn, Pb, Cd, Ni, Co, Mn, Fe, Cr and Cu was carried out by optical emission spectrophotometry using Inductively Coupled Plasma Optical Emission Spectrometry (ICP OES). Samples (sediment and fish) were collected from the Pirapó River at three different points (P1: near the source; P2: intermediate, close to the water collection point for public supply in the city of Maringá; P3: downstream from Maringá). The results showed concentration levels higher than the Maximum Residue Limit (MRL) for nine (9) of the twelve (12) elements in the sediment samples, including elements known for their high toxicity (Cr, Ni and Pb), in addition to those considered essential (Cu, Fe and Zn). For the fish samples, four (4) elements (Al, Cu, Hg and Zn) showed concentrations higher than the MRL. These results point to a high level of anthropogenic interference in these environments, configuring potential toxicity to the ichthyofauna of the Pirapó River and to the population supplied by the water of this river or that consumes fish.